The potential of industrial symbiosis in fostering sustainable entrepreneurship among the micro and small enterprises (MSEs): evidence from a developing country - Kimuli, Saadat Nakyejwe Lubowa; Sendawula, Kasimu; Najjinda, Shamirah; Nakimuli, Naqiyyah Kimuli (Emerald, 2023)
Purpose The purpose of this study is to explore the status and potential of industrial symbiosis in fostering sustainable entrepreneurship among micro and small enterprises (MSEs) in Uganda. Design/methodology/approach This study is cross-sectional and qualitative in nature. It involved conducting in-depth interviews with MSEs owners in Kampala, and data were analyzed using Atlasi Ti. Findings The results indicate that industrial symbiosis is a phenomenon that, notably, all MSE owners interviewed were practicing unknowingly, including recycling waste into sellable products, as well as sharing utilities, specialized machines and personnel for the smooth running of their businesses. In addition, participants expressed optimism that industrial symbiosis would be a major tool for business growth, innovation, employment opportunities, diversification and environmental protection for the benefit of the current and the future generations. Originality/value This study offers initial evidence on the status and potential of industrial symbiosis in fostering sustainable entrepreneurship among MSEs in Uganda